PENGARUH JUMLAH PRODUK DAN POLA PEMBELIAN TERHADAP DISTRIBUSI PRODUK PINTU UPVC PADA PT. SMART TECHTEX MEDAN - Retno Juniarti; Muhammad Asnawi; Mierna Zulkarnain (Journal Economic Management and Business, 2022)
Based on the results of the research with the t test, it is known that the tcount value of the variable number of products (X1) is 9.259 which is compared to ttable of 1.69092 which means 9.259 > 1.69092 so that H0 is rejected and Ha is accepted, which means that the variable number of products has a significant (significant) effect) with distribution variables. In addition, the results of the research using the t-test showed that the t-count value of the purchasing pattern variable (X2) was 2.467 which was compared to t-table 1.69092 meaning 2.467 > 1.69092 so that H0 was rejected and Ha was accepted, which means that the Purchasing Pattern variable had a significant effect (Significant). ) with distribution variables. Furthermore, the results of the research with the f test, it is known that the value of fcount = 4.389 which is compared with ftable of 3.26 means fcount > ftable (4,389 > 3,26) so H0 is rejected and Ha is accepted which means that the variable number of products and purchasing patterns together positive and significant effect on the distribution of UPVC door products at PT. Smart Techtex Medan. Based on the determination test, it is known that the percentage of the effect of the number of products (X1) and Purchase Pattern (X2) on the distribution (Y) is 0.823 or 82.3% while the remaining 17.7% is influenced by other factors not examined.